Necrophagy of a nurse shark (Ginglymostoma cirratum) by tiger sharks (Galeocerdo cuvier) - Rada, Danilo P.; Burgess, George H.; Rosa, Ricardo S.; Gadig, Otto B.F. [UNESP] (Editorial Pontificia Universidad Javeriana, 2015)
The aim of this study is to report a scavenging event, involving the consumption of a nurse shark, Ginglymostoma cirratum, by tiger sharks, Galeocerdo cuvier, at Fernando de Noronha archipelago, Brazil. Recreational divers found and photographed a bitten nurse shark carcass, just after sighting two tiger sharks near of the site. We estimated the sharks total lengths and discussed aspects of this feeding interaction using of images of forensic analysis. A straight cut on the nurse shark caudal fin, whose total length was estimated as 200 cm, suggest that it was caught by illegal fishing. A skin peeling process on the nurse shark fins indicates that the tiger sharks consumed it after its death, in a scavenging event. This is the first published report of a scavenging event involving the consumption of an elasmobranch by tiger sharks, allowing a better comprehension of tiger sharks' alimentary biology.
Keywords: Brazil; Carcharhinidae; Fernando de Noronha archipelago; Forensic analysis; Ginglymostoma; Scavenging behavior